Radiological and Anthropometrical Analysis of the Hip Joint Using Computed Tomography Scan in North Indian Population - Divya Nand Pandey; Ravi Garg; Chandan Kumar; Chetan Singh; Nayank Gautam (Journal of Orthopedics, Traumatology and Rehabilitation)
Background: Anthropometric research on the hip joint has significant clinical implications, including (1) implant design and (2) avoiding implant mismatch complications, such as aseptic loosening and incorrect load distribution, which are mainly unknown in North India. The aim of this research is to ascertain the anatomical differences in the normal hip joint across individuals in North India and to statistically compare the results with global data. Materials and Methods: We used one hip topogram and one axial segment of the femoral head to analyze 100 people (35 females and 65 males) with normal hips between the ages of 20 and 65. In both sexes and on both sides, we determined the means of the following measurements: femoral head diameter (HD), femoral neck width (NW), femoral neck length, acetabular angle of sharp, femoral version, horizontal offset, acetabular version, and vertical offset. Results: The following are the mean parameters that were observed: (a) neck shaft angle (NSA) - 128.93°, (b) femoral HD = 4.29 cm, (c) femoral NW = 2.97 cm, (d) femoral neck length = 3.61 cm, (e) Acetabular angle of Sharp - 33.01°, (f) Acetabular version = 20.44°, (g) femoral Version = 21.57°, (h) horizontal offset = 3.62 cm, and (i) Vertical offset = 4.43 cm. Conclusion: The NSA and acetabular angle of sharp were 5°–6° more when compared to the western population while horizontal and vertical offset is comparatively less than Western population and in the Indian NSA was higher for North Eastern population than the North Indian population. The residual parameters were comparable to those found in Western literature.